Religious Heritage Tourism: The St. Paul Trail Project in Troas - Boz, Mustafa (The international journal of religious tourism and pilgrimage, 2018)
oday many tourists wish to explore different cultures, and thus, visit cultural, historical and religious sites. The WTO estimates that each year between 300-330 million tourists visit the most important religious sites in the world. Religious tourism is purported to foster socio-economic development of host communities and promote awareness of the historical, cultural, traditional, and artistic heritage values of destinations. Host destinations increasingly create and offer cultural and religious routes as tourism products, so that the staying duration of tourists can be extended and revenues can be increased. One such destination, where religious / pilgrim tourism is growing in popularity is Turkey. This paper is a preparatory work of a project called The St. Paul Trail in Troas'. St. Paul was responsible for the spread of Jesus' message and Christianity throughout Asia Minor and Western Europe. St. Paul had 3 Missionary Journeys and one voyage to Rome. In his 2nd Missionary Journey to Greece (AD 50-52 or 49-52) (Acts 15:3618:22) and his 3rd Missionary Journey, Paul travelled to Asia and Greece. In AD 53-58 (or 54-58) (Acts 18:23-21:15) he visited and passed through the Troas region (today's Canakkale), raising a young Eutychus from the dead and meeting with Luke in Assos. The project has been accepted as a Future is in Tourism Project' which is supported by the UNDP (United Nations Development Programme), the Ministry of Culture and Tourism of Turkey, and Anadolu Group, as an important stage of the Troy Culture Route'. The St. Paul Trail starts from the ancient port of Alexandria Troas (Dalyan), where he landed on his 3rd Missionary Journey and follows his footsteps to the temple of Apollo Smintheion, ending at the ancient port of Assos where he boarded a boat to go to Lesbos. The trail will be about 60kms and in some places, it follows an original Roman route. The general objectives of the project are: the development of sustainable tourism in the region; supporting local development, to ensure not only economic growth but also socio-cultural development, and; to ensure the spread of tourism in all seasons. It is expected that a successfully constructed and promoted trail will attract many tourists from all over the world who wish to trace the history of their religion, visit Biblical places, and places linked to Homer's epic tales (The Iliad and Odysseus).